Role of Chronic Inflammation as a Predictor of Upstaging/Upgrading in Prostate Cancer: Finding a New Group Eligible for Active Surveillance - Nowroozi, Mohammad Reza; Ayati, Mohsen; Amini, Erfan; Aghamiri, Seyed Majid; Momeni, Seyed Ali; Ohadian Moghadam, Solmaz; Valizadeh, Farzin (Urology Journal, 2020)
Purpose: We aimed to investigate the correlation between presence of inflammation and pathology upgrading/upstaging in patients with prostate cancer. Materials and Methods: A retrospective study was accomplished on 315 patients with prostate cancer, eligible for active surveillance except prostate-specific antigen (PSA) level (PSA<30ng/dL), who underwent radical prostatectomy between 2005 and 2015. Patients were divided into two groups based on needle biopsy: A; with evidence of inflammation (chronic prostatitis) and B; without inflammation. The frequency of upstaging and upgrading in both groups was compared in different ranges of PSA level (<10, 10-20 and 20-30ng/dL). Upgrading/Upstaging was defined as increase from one prognostic grade group to another. Statistical analyses were performed to investigate the relation between inflammation and upgrading/upstaging. Results: The mean age of the patients was 68.2 years and the mean PSA level was 10.2 ng/mL. Chronic prostatitis was identified in 82 of 315 cases therefore upgrading/upstaging were seen in only three patients (3.7%) while 39 of 233 (16.7%) patients without inflammation had upgrading/upstaging in final pathology (P = 0.003). Other variables including the patient’s PSA before surgery, PSA density, and the presence of hypoechoic areas in ultrasound had a significant relationship with the incidence of postoperative upgrading/upstaging. Among studied variables, presence of inflammation in biopsies was found to be the most important predictor of upstaging/upgrading (OR: 0.205). Conclusion: Our data demonstrated that patients with concurrent prostatitis and PCa may have a better prognosis even if the PSA level is higher than 10ng/mL.